Predictors of active cancer thromboembolic outcomes. RIETE experience of the Khorana score in cancer-associated thrombosis. - Tafur AJ; Caprini JA; Cote L; Trujillo-Santos J; Del Toro J; Garcia-Bragado F; Tolosa C; Barillari G; Visona A; Monreal M; RIETE Investigators; Bosevski, M; et al. (Thieme, 2017)
Even though the Khorana risk score (KRS) has been validated to predict against the development of VTE among patients with cancer, it has a low positive predictive value. It is also unknown whether the score predicts outcomes in patients with cancer with established VTE. We selected a cohort of patients with active cancer from the RIETE (Registro Informatizado Enfermedad TromboEmbolica) registry to assess the prognostic value of the KRS at inception in predicting the likelihood of VTE recurrences, major bleeding and mortality during the course of anticoagulant therapy. We analysed 7948 consecutive patients with cancer-associated VTE. Of these, 2253 (28 %) scored 0 points, 4550 (57 %) 1-2 points and 1145 (14 %) scored ≥3 points. During the course of anticoagulation, amongst patient with low, moderate and high risk KRS, the rate of VTE recurrences was of 6.21 (95 %CI: 4.99-7.63), 11.2 (95 %CI: 9.91-12.7) and 19.4 (95 %CI: 15.4-24.1) events per 100 patient-years; the rate of major bleeding of 5.24 (95 %CI: 4.13-6.56), 10.3 (95 %CI: 9.02-11.7) and 19.4 (95 %CI: 15.4-24.1) bleeds per 100 patient-years and the mortality rate of 25.3 (95 %CI: 22.8-28.0), 58.5 (95 %CI: 55.5-61.7) and 120 (95 %CI: 110-131) deaths per 100 patient-years, respectively. The C-statistic was 0.53 (0.50-0.56) for recurrent VTE, 0.56 (95 %CI: 0.54-0.59) for major bleeding and 0.54 (95 %CI: 0.52-0.56) for death. In conclusion, most VTEs occur in patients with low or moderate risk scores. The KRS did not accurately predict VTE recurrence, major bleeding, or mortality among patients with cancer-associated thrombosis.
Keywords: cancer; mortality; prediction; recurrences; venous thrombosis